PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN SEJARAH KELAS XI IPS 1 DI SMA NEGERI 9 TANJUNG JABUNG TIMUR - EMILIANI EMILIANI (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2023)
The research aims to determine the increase in learning outcomes in history lessons through problem solving models in class XI.IPS.1 students of SMA Negeri 9 Tanjung Jabung Timur. The conventional learning process with lots of lectures in teaching results in students not being active in learning. To overcome these problems, efforts are made to apply a learning model, namely the problem solving model where students are given the opportunity to find problems and solve problems in classroom learning. This research method is Classroom Action Research (PTK) with research procedures covering the stages of planning, implementing, observing, and reflecting. This research was conducted at Tanjung Jabung Timur 9 Public High School in the 2022/2023 academic year. This study included all students of class XI.IPS.1 SMA Negeri 9 Tanjung Jabung Timur, totaling 29 students consisting of 14 male students and 15 female students. The object of this research is the application of problem solving models to improve student learning outcomes. Data collection techniques used observation, documentation, and tests. Analysis of the data obtained by calculating the percentage of completeness of the learning outcomes of students who are able to achieve KKM and the percentage of classical completeness that students are able to achieve in learning. The results showed that there was an increase in student learning outcomes in history lessons in class XI.IPS.1 SMA Negeri 9 Tanjung Jabung Timur. It can be seen the average increase and completeness of students from cycle to cycle. The average application of HOTS in the first cycle was 55.17%, then in the second cycle it increased by 75.21%. There was an increase of 75.27%. With the total classical completeness in cycle I of 34.48% or as many as 10 people, then cycle II increased to 34.48% with a total of 25 students. ABSTRAKPenelitian bertujuan untuk mengetahui peningkatan Hasil Belajar dalam pelajaran Sejarah melalui model problem solving pada siswa kelas XI.IPS.1 SMA Negeri 9 Tanjung Jabung Timur. Proses pembelajaran yang konvensional dengan banyak ceramah dalam mengajar mengakibatkan siswa tidak aktif dalam belajar. Untuk mengatasi permasalahan tersebut dilakukan upaya dengan menerapkan suatu model pembelajaran yaitu model problem solving dimana siswa diberikan kesempatan untuk menemukan masalah dan menyelesaikan masalah dalam pembelajaran di kelas. Metode Penelitian ini adalah Penelitian Tindakan Kelas (PTK) dengan prosedur penelitian meliputi tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Penelitian ini dilakukan di SMA Negeri 9 Tanjung Jabung Timur tahun pelajaran 2022/2023. Penelitian ini adalah seluruh siswa kelas XI.IPS.1 SMA Negeri 9 Tanjung Jabung Timur yang berjumlah 29 siswa yang terdiri dari 14 siswa laki-laki dan 15 siswa perempuan. Objek penelitian ini adalah penerapan model problem solving untuk meningkatkan hasil belajar siswa. Teknik pengumpulan data yang digunakan observasi, dokumentasi, dan tes. Analisis data yang diperoleh dengan cara menghitung persentase ketuntasan hasil belajar siswa yang mampu mencapai KKM serta persentase ketuntasan klasikal yang mampu dicapai siswa dalam belajar. Hasil penelitian menunjukkan bahwa terdapat peningkatan hasil belajar siswa dalam pelajaran Sejarah pada siswa kelas XI.IPS.1 SMA Negeri 9 Tanjung Jabung Timur. Hal tersebut dapat diketahui rata-rata kenaikan dan ketuntasan siswa dari siklus ke siklus. Penerapan HOTS Rata-rata pada siklus I sebanyak 55,17% ,kemudian pada siklus II mengalami peningkatan sebesar 75,21%. Terjadi kenaikan sebesar 75,27%. Dengan jumlah ketuntasan klasikal disiklus I 34,48% atau sebanyak 10 orang, kemudian disiklus II mengalami peningkatan menjadi 34,48% dengan jumlah siswa sebanyak 25 orang.